Chimpanzee (Pan troglodytes) anticipation of food return: coping with waiting time in an exchange task - Dufour, V; Pelé, M; Sterck, E H M; Thierry, B (Journal of comparative psychology (1983), 2007)
Despite controversial expectations that animals achieve reciprocal altruism, it is unclear if nonhuman species possess the necessary cognitive abilities. For reciprocal altruism, individuals must anticipate the loss of a commodity and accept a delay before some return. The authors investigated the abilities of 5 chimpanzees (Pan troglodytes) to cope with increasing waiting duration in exchange tasks. Subjects had to keep a small cookie before returning it to a human partner to obtain a larger piece. For a piece 2, 4, or 8 times the size of the small piece, 3 of the 5 subjects waited for up to 4 min. For a piece 40 times larger, 4 of the 5 subjects waited up to 8 min. At long time lag, renouncement to wait occurred earlier than predicted by subjects' general waiting capacity, suggesting that the decision to wait was based on a trade-off between reward quantity and expected costs of the waiting duration. Chimpanzees could anticipate a delayed reward at a time scale of several minutes. If this reflects a cognitive limit in chimpanzees' anticipation capacity, reciprocal altruism by keeping track of costs and benefits over extended periods may be unlikely in chimpanzees.